Effect of microalgae (Tetraselmis chui Butcher 1959) on growth and survival of nile tilapia (Oreochromis niloticus Linnaeus 1758) reared in low salinity biofloc system - Wa Iba; Neneng Wahyuni; Muhaimin Hamzah; Michael A. Rice (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2024)
Addition of microalgae in the biofloc system may improve growth and survival of Nile tilapia. Also, culturing Nile tilapia in saline water biofloc system may be an adaptation for freshwater shortage. In this study, the growth and survival of Nile tilapia cultured in a low salinity biofloc system with added microalgae was investigated. Increasing salinity in the culture system was done by gradually adding sea water into acclimatization container (618 L, v) on weekly basis for 4 weeks until 9 psu salinity was reached. Tilapia were allowed to adapt to salinity change for one week and fed with commercial feed twice a day until satiation. The biofloc experiment was conducted with 3 microalgal density treatments (5, 15 and 25 104 cells. mL-1) in triplicates. Average initial weight of experimental fish was 4.82 0.76 g. Tilapia were reared for 40 days in aquaria (35 35 40 cm, l w h, 15 L, v) containing 8 individuals fish in each aquarium. The commercial pellets were delivered twice per day at 5% of tilapia biomass until satiation. T. chui was added to the tilapia culture every week. This study showed that the addition of microalgae did not affect the fish weight gain, specific growth rate and survival (p0.05). However, feed conversion ratio and culture productivity were better in tilapia supplied with weekly addition of T. chui at 15 104 cells mL-1 compared to other densities tested.Keywords:SalineBioflocMicroalgae